laparoscopic subtotal cholecystectomy a salvageable procedure in patients with comorbidities - Ashok Kumar*, Shomnath Reddy, Anu behari, V.K kapoor, Anand Prakash (Innovative Journal of Medical and Health Sciences, 2020)
Aim: Our aim of study to show the feasibility and outcomes of laparoscopic subtotal cholecystectomy in presence of difficult calot’s triangle anatomy, even in presence of cormobidities. Materials & Methods: This study involved a retrospective analysis of patients managed by laparoscopic subtotal cholecystectomy from January 2014 to December 2019. Here we analyzed the demography, indications, associated comorbidity, complications, management and their outcomes. Results: During this study period 53 cases underwent LSTC (laparoscopic subtotal cholecystectomy), Median age of patients was 52 years (range 31-76 years). 33 (62.26%) frozen calot’s triangle was the main peroperative findings in these cases. The infundibulum of gall bladder was mainly managed by endosuturing of the stump (n=21) rest of cases managed by an Endo GIA (n=7), serial metallic clipping (n=2) and in 4 cases stump was left unsutured with one subhepatic drain placement, 1 case omentum sutured over the cystic duct stump another 1 case of cholecystoduodenal fistula was repair with vicryl 3-0. There were (n=18) type I, (n=24) type II, (n=11) type III laparoscopic subtotal cholecystectomy done in our study. Two (3.77%) patients had postoperative morbidity. 1 (1.88%) case had a postoperative bile leak which was successfully managed by ERC and stenting. None of the case had a wound infection or intra abdominal collection; there was no mortality and no bile duct injury. The median postoperative stay was 4 days (range 2-16 days). The mean follow up duration was 60 months and the outcome was excellent in all the patients. Abbreviation: ERC (Endoscopic Retrograde Cholangiography), LSC (Laparoscopic Subtotal Cholecystectomy), GB (Gall Bladder), Conclusions: In scenario of difficult calot’s triangle, laparoscopic subtotal cholecystectomy is an effective and safe option, which shows excellent postoperative recovery and ensures a satisfactory functional outcome for the patient gall stone disease even in presence of comorbidities. Clinical Significance: KEYWORDS Laparoscopic cholecystectomy, Laparoscopic Subtotal cholecystectomy, difficult cholecystectomy.